Prescription factors influencing baloxavir prescription during the 2018/2019 and 2019/2020 seasons: a administrative database study in Japan - Naomi Fujiwara; Takashi Fujiwara; Yuya Ise (BMC, 2023)
Abstract Background We aimed to evaluate the factors associated with baloxavir prescription in Japanese hospitals using a health insurance claim-based database (MDV analyzer), during the 2018/2019 and 2019/2020 influenza seasons. The MDV analyzer contains anonymized claims data from approximately 420 Diagnosis Procedure Combination hospitals, and does not contain data from clinics. Methods Data were collected for influenza patients treated with anti-influenza drugs during the 2018/2019 and 2019/2020 influenza seasons. Multivariate analysis was used to identify factors associated with baloxavir prescription. Results During the study period, 322,063 influenza patients were included for analyses. In multivariate analysis, children, female sex, inpatient, hospital bed capacity, and private hospitals were negatively associated with baloxavir prescription. Compared to elderly patients, the adjusted odds ratio (OR) for baloxavir prescription was 0.612 (95% confidence interval (CI), 0.587-0.637) in children aged 6-11 years, and 0.119 (95% CI, 0.111-0.128) in children aged 0-5 years. Compared to small hospitals (bed capacity, 20-299), the adjusted OR for baloxavir prescription was 0.559 (95% CI, 0.540-0.578) in large hospitals (bed capacity, ≥ 500). Conclusion Children, female sex, inpatient, hospital bed capacity, and private hospitals were negatively associated with baloxavir prescription.